在下列反应中,焓变等于AgBr(s)的的反应是()
A: Ag+(aq)+Br-(aq)→AgBr(S)
B: 2Ag(s)+Br2(g)→2AgBr(s)
C: A
A: Ag+(aq)+Br-(aq)→AgBr(S)
B: 2Ag(s)+Br2(g)→2AgBr(s)
C: A
举一反三
- 在下列反应中,焓变等于AgBr(s)的ΔfHmθ的反应是()。 A: Ag+(aq)+Br-(aq)AgBr(s) B: 2Ag(s)+Br2(g)2AgBr(s) C: Ag(s)+Br2(l)AgBr(s) D: Ag(aq)+Br2(g)AgBr(s)
- 在下列反应中,焓变等于AgBr(s)的ΔfHmθ的反应是()。 A: Ag+(aq)+Br-(aq)AgBr(s) B: 2Ag(s)+Br2(g)2AgBr(s) C: Ag(s)+Br2(l)AgBr(s) D: Ag(aq)+Br2(g)AgBr(s)
- 在下列反应中,焓变等于AgBr(s)的的反应是: A: Ag+(aq)+Br-(aq)=AgBr(s) B: 2Ag(s)+Br2(g)=2AgBr(s) C: Ag(s)+Br2(l)=AgBr(s) D: Ag(s)+Br2(g)=AgBr(s)
- 在下列反应中,焓变等于AgBr(s) 的∆fHmq的反应是( ) A: Ag+(aq) + Br-(aq) = AgBr(s) B: 2Ag(s) + Br2(g) = 2AgBr(s) C: Ag(s) +½Br2(l) = AgBr(s) D: Ag(s) +½Br2(g) = AgBr(s)
- 在下列反应中,焓变等于AgBr(s)的ΔfHmΘ的反应是 A: Ag+(aq)+Br-(aq)=AgBr(s) B: 2 Ag(s)+Br2(g)=2 AgBr(s) C: Ag(s)+1/2 Br2(l)=AgBr(s) D: Ag(s)+1/2 Br2(g)=AgBr(s)